2006
DOI: 10.1095/biolreprod.105.046557
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Porcine Endometrial Prostaglandin Synthase During the Estrous Cycle and Early Pregnancy, and Following Endocrine Disruption of Pregnancy1

Abstract: Porcine trophoblast attachment to the uterine surface is associated with increased conceptus and endometrial production of prostaglandins. Conceptus secretion of estrogen on Day 12 of gestation is important for establishment of pregnancy; however, early (Days 9 and 10) exposure to exogenous estrogens results in embryonic mortality. Present studies established the temporal and spatial pattern of endometrial PTGS1 (prostaglandin-endoperoxide synthase 1) and PTGS2 expression during the estrous cycle and early pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
60
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 40 publications
5
60
0
Order By: Relevance
“…Moreover, PGE 2 can be converted into PGF 2a by PG 9-ketoreductase/carbonyl reductase (CBR1). It was demonstrated that highly inducible forms of PTGS and PGE synthase in the porcine endometrium are PTGS2 (also known as PGHS-2 or COX-2; Ashworth et al 2006) and microsomal PGE synthase-1 (mPGES-1), respectively (Waclawik et al 2006).…”
Section: Role Of Pgs During Pregnancy Establishmentmentioning
confidence: 99%
“…Moreover, PGE 2 can be converted into PGF 2a by PG 9-ketoreductase/carbonyl reductase (CBR1). It was demonstrated that highly inducible forms of PTGS and PGE synthase in the porcine endometrium are PTGS2 (also known as PGHS-2 or COX-2; Ashworth et al 2006) and microsomal PGE synthase-1 (mPGES-1), respectively (Waclawik et al 2006).…”
Section: Role Of Pgs During Pregnancy Establishmentmentioning
confidence: 99%
“…In addition, conceptus estrogens modulate uterine gene expression responsible for uterine remodeling for implantation and placentation from days 13 to 25 of gestation (25). The importance of estrogen is underscored by the fact that premature exposure of the pregnant uterus to estrogen on days 9 and 10 results in degeneration of all pig conceptuses by day 15 (26).…”
mentioning
confidence: 99%
“…In gilts, developing conceptuses secrete estrogens to signal its presence in the uterus [34], and the profile of E2 secretion by developing embryos coincides with estrogen receptor expression in the endometrium [32]. Changes occurred in the endometrium as a result of conceptus estrogen secretion include increased PGHS-2 expression [20,21] and PGE2 secretion [35]. The existence of the Hoxa10 / Pghs2 / PGE2 axis has previously been shown in uterine tissues of mice.…”
Section: Steroids Modulate Hoxa10 Expression In the Pigmentioning
confidence: 92%
“…The rate-limiting enzyme in PG production is prostaglandin H synthase (PGHS; also known as cyclooxygenase), which catalyzes the conversion of arachidonic acid to PGH2 [19], the common substrate for various PGs. Expression of PGHS-2 in the endometria of cyclic and early pregnant gilts has previously been demonstrated [20,21]. Interestingly, Hoxa10 null mice lack Pghs2 expression in stromal cells of the endometrium.…”
mentioning
confidence: 89%